Optimalisasi Turbin Angin Darrieus dengan Variasi Perbandingan Jumlah Sudu - Muhammad Suprapto; Idzani Muttaqin (Jurnal Sains dan Teknologi, 2024)
Wind energy is a renewable energy that has the potential to be developed as an electricity generator. Indonesia has the potential for wind energy throughout the year but the wind speed is still classified as low wind speed. Development of a small scale Darrieus wind turbine that can operate at low wind speeds. In this research, variations in the number of blades 2, 3 and 4 are the focus to improve the performance of the Darrieus wind turbine. Testing at a wind speed of 3.4 m/s, the turbine with 2 blades had the highest rotation value of 128 Rpm, 4 blades had a rotation value of 98.6 and the lowest rotation result was 3 blades with a rotation value of 76.5 Rpm.